STUDY OF WATER BALANCE AND WATER QUALITY ON HIDROLOGICAL SYSTEM OF BETON SPRING FOR WATER RESOURCE CONSERVATION IN DISTRICT PONJONG, GUNUNGKIDUL REGENCY - , YUMI LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Beton Spring is an outlet or resurgence of surface stream hydrological sytem that sinked into swallow holes in karst region. Pentung, Gayam, and Tesih river was predicted as allogenic input of Beton Spring. The Discharge of Beton Spring is relatively large, with conduit stream that tends to turbulence and perennial. The main function of itâs discharge is for irrigated 1250 hectares wet rice field within 3 district, and another functions is for fisheries and domestic use. Residents within recharge area of Beton Spring utilizing stream discharge, springs, and caves that predicted as the same system as Beton Spring for various purposes. Limestone mining was commonplace in a karst region, so that sustainability of Beton Spring discharge and it's water quality are threatened. \"The Study of Water Balance and Water Quality of Beton spring Hydrological Systems for Water Resource Conservation within Ponjong District, Gunungkidul Regency\" aims to 1) determine the indicative catchment area of Beton Spring, 2) calculate water balance, 3) water quality analyzes for fisheries, and 4) water resources conservation strategy. The methods that used in this study were divided into method of sampling and data collection. Area sampling method was used for landuse checking and purposive sampling used for the interviews. Morphological analysis using contour maps for delineation, water balance analysis, matching the suitability of water quality for fisheries, and the criticality identification of catchment areas to set the strategies of land and discharge management. The boundary of indicative catchment area of Beton Spring is entire the rainwater catchment that flowing into Pentung, Gayam, and Tesih River which is only 1678 hectares. This Boundary verified with water balance analysis, analysis of geological map, and field checking. Beton Spring average discharge is 0,72 m3/sec with effective rainfall (P- Ep) up to 468 mm, so that the dimension of cathment area is 4841 hectares, wider than indicative boundary of water catchment. Boundary of Beton spring catchment area is abreast to 5 allogenic catchment area among Pentung, Gayam, Tesih, Kedung Paran, Plalar River and autogenic catchment areas. Beton Spring water quality is suitable for freshwater fish farming with limiting factors of to 468 mm, so that the dimension of cathment area is 4841 hectares, wider than indicative boundary phosphate and temperatures. Land management focused on allogenic water catchment and partially autogenic catchment that extent to 3170 hectares (65,5%). 72,4 % of Recharge area condition is in good category to natural normal, 27,6 % is almost critical and rather critical category. Qualitatively discharge management is already good because there are sufficient discharge quantity and good water quality.